The global perspective on income inequality - Arthur Zito Guerriero; Jakob Kapeller (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2024)
This paper provides a comprehensive overview of the ongoing debate on global income inequality. It shows that global income inequality is a valuable analytical concept that significantly enhances our understanding of global economic dynamics. By addressing key methodological issues in the measurement of global income inequality, the paper compares different datasets used in the literature and conducts an exploratory analysis of recent trends. This analysis re-evaluates the relative impact of inequality between and within countries and highlights how growth and distributional dynamics in specific countries influence global income inequality.
Keywords: D31; F01; F60; 330; income inequality; globalization; measurement of inequality; convergence